Bilgi Teknolojileri ve Dijitalleşmenin Türkiye'de Bilgibilim Literatürüne Yansıması:Bilgi Dünyası Dergisi Örneği (2000-2014) - (:unkn) unknown (My University, 2016)
Bilgi ve Belge yönetimi alanı, bilgi teknolojileri ve dijitalleşmeden en çok etkilenen disiplinlerden biri durumundadır. Bilgi teknolojileri ve dijitalleşme, kütüphane ve bilgi merkezlerinde yapılan uygulamaların teknik boyutunu arttırırken; bilimsel bir disiplin olarak Bilgi ve Belge yönetimi'nin de çalışma sahasını ve disiplinlerarası araştırma fırsatlarını genişletmiştir. Bu durum Türkiye'deki bilimsel dergilere de yansımıştır. Bu çalışmada; Türkiye'nin önde gelen bilgibilim dergilerinden olan Bilgi Dünyası Dergisi'nin 2000-2014 tarih aralığındaki yayın birikimi sistematik olarak analiz edilmiştir. araştırma sonunda 182 hakemli makalenin %45; 87 görüş yazısının ise %33 oranında bilgi teknolojileri, dijitalleşme ve dijital kültür konularıyla ilgili olduğu görülmüştür.

The ınformation and records Management field, has been one of the disciplines that affected by information technologies and digitization to a great extent. While improving the technical aspects of the work undertaken in libraries and information centers, information technology and digitization has also expanded the scope of the ınformation and records Management field and opened up interdisciplinary research opportunities. This trend can be observed in the scientific journals in Turkey. ın this study, the accumulation of publications between 2000 and 2014 in one of the Turkey's foremost information science journals, ınformation World Journal, has been systematically analyzed. The results of this study indicates that 45% of 182 peer-reviewed articles and 33% of 87 opinion papers has been related to the topics of information technology, digitization and digital culture.
Reflection of Information Technology and Digitization on the Information Science Literature In Turkey: The Case of Information World Journal (2000-2014)
Keywords: Bilgi, Belge Yönetimi